Fiber, prebiotics, and diarrhea: what, why, when and how. Issue 5 (September 2016) - Generoso, Simone de Vasconcelos; Lages, Priscilla Ceci; Correia, Maria Isabel T.D.
Abstract : Purpose of review: Dietary fiber and prebiotics have been the focus of research and discussion for decades, but there are still pending concepts and definitions, in particular when addressing their use in the prevention and treatment of diarrhea. The purpose of this review is to present the latest advances in the understanding of dietary fiber and prebiotics, to review their proven role in the management of diarrhea, and to postulate the best timings and optimal doses. Recent findings: The use of prebiotics has encompassed not only prevention but also the treatment of distinct types of diarrhea, at different treatment moments, and with regard to various different markers of outcome. Furthermore, the description of soluble fibers claiming to be prebiotics, and vice versa, has too often been the tone in the literature, which has led to misconceptions in classification and, consequently, confusion over the interpretation of results. It remains difficult to establish a consensus about the real impact of fiber and prebiotics on the prevention and therapy of diarrhea. Summary: The review highlights the overlapping concepts of fiber and prebiotics, and supports the need for adequate individualization of their use, according to the goal – either prevention or treatment of diarrhea – as well as the optimal timing and dose to be used. Nonetheless, viscous soluble fibers seem to be the best option in treating diarrhea, whereas prebiotics are more important in preventing and avoiding recurrence.